A Flexible Tool for Joining Technologies — The Diode Laser. Issue 1 (January 2014) - Reinl, Steffen
Abstract In the history of lasers, the diode laser is the most recent technology development for industrial applications. Driven by technology improvements, the diode laser has enormous potential in penetrating more and more industrial markets within a short time frame. It has replaced applications that were typically reserved for solid‐state lasers and has the capacity to actually generate better results due to its unique beam parameters. With Dilas' long‐term market history and experience, diode lasers are finding greater uses specifically for industrial usage. The latest generation series demonstrates this development and sets new standards in regard to highest reliability due to passive cooling technology. Within this article, new possibilities in the field of plastics welding, welding of thin sheet metals and soldering will be discussed.